THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT BUNTU TURUNAN VILLAGE OFFICE, HATONDUAN SUB-DISTRICT, SIMALUNGUN DISTRICT - Edy Erianto (Jurnal Ilmiah Akomodasi Agung, 2023)
This study aims to determine whether there is an influence between work discipline on employee performance in Buntu Turunan Village, Hatonduhan District, Simalungun Regency. The population in this study were all employees at the Buntu Turunan village office, Hatonduhan District, Simalungun district, and the sample was determined purposively. The research method used in this study is a quantitative descriptive method. Based on the results of the analysis that has been carried out, it shows that the work discipline variable has a positive effect on employee performance at the Buntu Turunan village office, Hatonduhan District, Simalungun district. The magnitude of the contribution of work discipline to employee performance can be said to be significant from the analysis that has been carried out at the Buntu Turunan village office, Hatonduhan District, Simalungun district